2018
DOI: 10.1111/ijau.12120
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the association between the content of internal audit disclosures and external audit fees: Evidence from Sweden

Abstract: The aim of this study is to explore the content of internal audit (IA) disclosures in annual reports and explain the relationship between IA disclosures and external audit fees. A content analysis of the IA disclosures made it possible to generate inductive categories that were used as a basis for statistical analysis. The findings show a large variation in disclosure practices, and only a small portion of all disclosures contain firm‐specific information related to IA. Evidence is provided that the use of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 64 publications
(158 reference statements)
0
14
0
7
Order By: Relevance
“…If the internal auditors comply with these standards, the external audit fee will also increase. As well as research Laura Sierra, Garcia., Et. al., (2018) which states that the internal audit function has a positive effect on the costs of external auditors.…”
Section: The Effect Of Internal Audit Disclosure (Dia) On External Audit Feesmentioning
confidence: 99%
See 1 more Smart Citation
“…If the internal auditors comply with these standards, the external audit fee will also increase. As well as research Laura Sierra, Garcia., Et. al., (2018) which states that the internal audit function has a positive effect on the costs of external auditors.…”
Section: The Effect Of Internal Audit Disclosure (Dia) On External Audit Feesmentioning
confidence: 99%
“…The results of this study are supported by research by Sourour Hazami-Ammar (2019) which confirms that increased internal audit working hours have a significant positive effect on external audit costs. As well as research Laura Sierra, Garcia., Et. al., (2018) emphasized that the internal audit function has a positive effect on the costs of the external auditor.…”
Section: The Effect Of Internal Audit Disclosure (Dia) On External Audit Feesmentioning
confidence: 99%
“…Other research showed that there is a relationship between internal audit disclosures in financial statements and external audit costs [52]. Companies that disclose information related to internal audits specifically and informatively indicate that there is an increase in the quality of corporate governance [53], and with strong corporate governance, it is shown a higher quality of internal audit functions and are prepared to pay for higher quality external audits [52,54]. Increases in risk management, internal control processes and high internal audit function quality can reduce the time and effort of external auditors in carrying out their duties, and thus the audit fees incurred will be lower [20,52].…”
Section: Internal Audit Relationship In Determining Audit Fees For Exmentioning
confidence: 99%
“…Other research showed that there is a relationship between internal audit disclosures in financial statements and external audit costs [52]. Companies that disclose information related to internal audits specifically and informatively indicate that there is an increase in the quality of corporate governance [53], and with strong corporate governance, it is shown a higher quality of internal audit functions and are prepared to pay for higher quality external audits [52,54].…”
Section: Internal Audit Relationship In Determining Audit Fees For Exmentioning
confidence: 99%
See 1 more Smart Citation